The legislative framework for salt iodization in Asia and the Pacific and its impact on programme implementation. Issue 16 (7th September 2017) - Codling, Karen; Rudert, Christiane; Bégin, France; Peña-Rosas, Juan Pablo
Abstract: Objective: Fortification of food-grade (edible) salt with iodine is recommended as a safe, cost-effective and sustainable strategy for the prevention of iodine-deficiency disorders. The present paper examines the legislative framework for salt iodization in Asian countries. Design: We reviewed salt iodization legislation in thirty-six countries in Asia and the Pacific. We obtained copies of existing and draft legislation for salt iodization from UNICEF country offices and the WHO's Global Database of Implementation of Nutrition Actions. We compiled legislation details by country and report on commonalities and gaps using a standardized form. The association between type of legislation and availability of iodized salt in households was assessed. Results: We identified twenty-one countries with existing salt iodization legislation, of which eighteen were mandatory. A further nine countries have draft legislation. The majority of countries with draft and existing legislation used a mandatory standard or technical regulation for iodized salt under their Food Act/Law. The remainder have developed a 'stand-alone' Law/Act. Available national surveys indicate that the proportion of households consuming adequately iodized salt was lowest in countries with no, draft or voluntary legislation, and highest in those where the legislation was based on mandatory regulations under Food Acts/Laws. Conclusions: Legislation for salt iodization, particularly mandatory legislation under the national food law, facilitates universal salt iodization. However, additional important factors for implementation of salt iodization and maintenance of achievements include the salt industry's structure and capacity to adequately fortify, and official commitment and capacity to enforce national legislation.